Chronolgical changes in meiotic status and protein synthesis requirement for nuclear maturation of buffalo (Bubalus bubaiis) oocytes - NIGAM, R; LAKHCHAURA, B D; LAXMICHAND, LAXMICHAND; MAURYA, S N (The Indian Journal of Animal Sciences, 2013)
Chronological examination of maturing buffalo oocytes was undertaken in order to examine the relationship between protein synthesis requirement and meiotic events. The buffalo oocytes were incubated in 50 oil drops of maturation medium under paraffin oil at 39Â°C with 5% CO2 in humidified air for 27 hr. The chromosomal status of oocytes was determined by fixing them at every 3 hr intervals from 0 to 27 hr or at 27 hr after addition of cycloheximide (10ig/ml) at specific time intervals. Eighty three per cent oocytes were found in germinal vesicle (GV) stage at 0 hr. The germinal vesicle breakdown (GVBD) occurred at 6 hr, chromatin condensation (CC) between 9-12 hr, metaphase-I (M-I) at 12 hr, anatelophase (A-T) between 15-18 hr and metaphase-II (M-II) between 24-27 hr of culturing. Cycloheximide blocked oocyte maturation at GVBD, CC and M-I when present from 0-3 hr, 6-9 hrand 9-12 hrfrom time of culturing respectively. A large number of oocytes, however, were found in unidentified stage, when the inhibitor was present during 12-18 hr post-culturing. Based on these results, it is proposed that protein synthesis is required at least for 3 different steps in oocyte maturation.